Human mortality attributable to outdoor air pollution in China during the period 2016-2020 - Gang Liu; Lingling Jiang; Zhuoying Xu; Yifan Liu; Haikun Wang; Zhen Peng (IOP Publishing, 2023)
In this study, a latest reanalysis dataset of atmospheric composition, the Global Exposure Mortality Model and a log-linear exposure-response function were employed to estimate the national deaths attributable to fine particulate matter (PM _2.5 ) and ozone (O _3 ) pollution in China for the period 2016-2020, including the lockdown due to COVID-19 pandemic in 2020. The national mortality attributable to long-term PM _2.5 exposure decreased year by year from 2.18 million (95% confidence interval (1.83, 2.51), the same hereinafter) in 2016 to 1.99 million (1.66, 2.30) in 2020. In particular, the number in 2020 was 133.16 thousand less than 2019 owing to the reduced emissions during the pandemic, and the mortality attributable to short-term PM _2.5 exposure dropped from 46.86 thousand in 2019 to 36.56 thousand in 2020. However, because O _3 concentrations have kept increasing during the period, the national mortality attributable to long-term O _3 exposure increased from 132.79 thousand (128.58, 137.00) in 2016 to 197.00 thousand (190.98, 203.03) in 2020. In addition, compared to before the pandemic, the national mortality attributable to short-term O _3 exposure showed an increase in February, April and May of 2020, and the sharpest year-on-year increase of 162% occurred in April. The different trends of mortality after anthropogenic emissions were reduced pose a challenge for policy-makers and researchers.